Superelasticity and cryogenic linear shape memory effects of CaFe2As2 - John T. Sypek (Nature Portfolio, 2017)
Shape memory materials are capable of returning to their original form post-deformation, but those with high actuation performances remain scarce. Here the authors reveal that CaFe2As2 exhibits cryogenic linear shape memory behaviour with high recoverable strain and yield strength, owing to a reversible uni-axial phase transformation.